Lighting shadows: Approaches and experiences for accessible heritage - Stang, José Ignacio; Pezza, Agustina (Estoa. Journal of the Faculty of Architecture and Urbanism, 2019)
The investigation Illuminating Shadows seeks to provide people with visual disabilities with the necessary resources so that, during a visit to a building of the built heritage of the city of Cordoba, Argentina, they can imagine what the reality that they have in front of them is like and what it contains, aspiring to have each one manage their own route. This paper presents theoretical and methodological reflections on this subject, and the results of their application after a first visit experience. In a qualitative sense, the approach chosen as a methodological modality is Study-Action, which implies a special epistemology and nosological perspective. In addition, a perspective and experiential logic of active conservation was adopted, where the objective is the enrichment of the collective memory, the recognition of its authenticity and changing values, and its appropriation by the community.